2022
DOI: 10.1155/2022/6160701
|View full text |Cite
|
Sign up to set email alerts
|

Dexpramipexole Attenuates White Matter Injury to Facilitate Locomotion and Motor Coordination Recovery via Reducing Ferroptosis after Intracerebral Hemorrhage

Abstract: Deciphering the factors causing damage to white matter fiber bundles and exploring new strategies to alleviate white matter injury (WMI) is a promising treatment to improve neurological impairments after intracerebral hemorrhage (ICH). Ferroptosis usually occurs at perihematomal region and contributes to neuronal death due to reactive oxygen species (ROS) production. Dexpramipexole (DPX) easily crosses the blood brain barrier (BBB) and exerts antioxidative properties by reducing ROS production, while the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…First, the Kv1.3 blockade promotes the regenerative ability resulting from neural progenitor cell (NPC), as previous study has indicated the administration of Kv1.3 inhibitor promotes NPC proliferation after brain injury [14]. Second, the administration of PAP-1 promotes oligodendrocyte progenitor cell (OPC) proliferation and differentiation into oligodendrocyte, which are responsible for myelination in the CNS [7], through increasing AKT activation [45]. Third, the application of PAP-1 increased the neurotrophic factors (including NGF and BDNF) around hematoma, which support neuron survival [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the Kv1.3 blockade promotes the regenerative ability resulting from neural progenitor cell (NPC), as previous study has indicated the administration of Kv1.3 inhibitor promotes NPC proliferation after brain injury [14]. Second, the administration of PAP-1 promotes oligodendrocyte progenitor cell (OPC) proliferation and differentiation into oligodendrocyte, which are responsible for myelination in the CNS [7], through increasing AKT activation [45]. Third, the application of PAP-1 increased the neurotrophic factors (including NGF and BDNF) around hematoma, which support neuron survival [46].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the long-term disability possibly ascribes to the white matter injury (WMI) in basal ganglia [3]. Our previous studies have illustrated that the integrity of white matter ber bundles is a promotor for functional recovery [4][5][6], and a series of strategies, such as the inhibition of ferroptosis with the administration of dexpramipexole (DPX) [7], upregulation of brain-derived neurotrophic factor (BDNF) by lithium [8], and inactivation of microglia into M1 phenotype using ambroxol [9], have been corroborated to accelerate functional recovery through mitigating WMI after ICH.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed in the FSP1/CoQ10 antioxidant system that the level of FSP1 was significantly reduced in the brain tissue surrounding hematomas in ICH mice, which could be treated with the drug dexpramipexole to reverse this harmful change ( Wang B. et al, 2022 ). However, the expression pattern and the underlying mechanism with the potential role of CoQ10 have not been adequately investigated.…”
Section: The Research Status In Ferroptosis In Hemorrhagic Strokementioning
confidence: 99%
“…Subsequently, they further systematically presented ample evidence of ferroptosis in oligodendrocytes after ICH ( Shen et al, 2022 ). Dexpramipexole has also been reported to attenuate white matter damage caused by oligodendrocyte ferroptosis in mice after ICH, thereby improving spatial localization and motor function ( Wang B. et al, 2022 ). Moreover, ferroptosis has also been reported to be involved in white matter damage after spinal cord injury, which can be suppressed by the application of Fer-1 ( Chen et al, 2022 ).…”
Section: The Research Dilemma and Prospects Of Ferroptosismentioning
confidence: 99%
“…Pharmacokinetic studies have demonstrated that DPX is clinically safe and well-tolerated [22]. DPX can easily cross the blood-brain barrier and accumulate within the brain [23][24][25]. Moreover, DPX has been found to improve mitochondrial efficiency, decrease ROS production, suppress apoptosis and increase cell survival, thus exerting neuroprotective effects in animal models of stroke and progressive multiple sclerosis [26,27].…”
Section: Introductionmentioning
confidence: 99%